PERTANGGUNGJAWABAN DOKTER FORENSIK DALAM TINDAK PIDANA PEMALSUAN VISUM ET REPERTUM - R. Aj Dwi Sukmaningru Hayati; Made Warka (Gapenas Publisher, 2023)
In the case of a post mortem investigation, it is very important to have it as a complement to the evidence of a case, as well as the family of the victim, which is used to complement the evidence of a case and reveal a case, which with the help of experts can make it easier in terms of handling which authority What is given to investigators is a law aimed at submitting expert testimony. The situation of Visum Et Repertum can be said to be important which is to overcome legal problems, namely the obstacles that occur, namely for investigators to be able to immediately make a request letter for Visum Et Repertum to victims who are asked to the doctor if there are victims who need to be asked for Visum Et Repertum to be examined immediately and preferably, for the family it is hoped that they can give permission to do a post-mortem for the purposes of investigation, and for the hospital so that the making of Visum Et Repertum can run smoothly. The purpose of this research is to find out the responsibility of the forensic doctor in the criminal act of counterfeiting in visum et repertum. In this study, using normative juridical methods were examined with library data which included primary and secondary laws